2015
DOI: 10.1007/s13760-015-0499-8
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of epilepsy caused by POLG mutations

Abstract: Mutations in POLG are increasingly recognized as a cause of refractory occipital lobe epilepsy (OLE) and status epilepticus (SE). Our aim was to describe the epilepsy syndrome in seven patients with POLG mutations. We retrospectively reviewed the medical records of seven patients with POLG mutations and epilepsy. Mutation analysis was performed by direct sequencing of the coding exons of the POLG gene. Disease onset was at a median age of 18 years (range 12-26). Epilepsy was the presenting problem in six patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…69 Our result is consistent with previous observations of a predisposition for occipital lobe involvement in POLGrelated epilepsy, especially among those with juvenile and adult onset, in terms of clinical, radiologic, and histopathologic findings; however, the precise explanation of such preferential involvement remains enigmatic. 12,70 The stroke-like lesions in POLG-related epilepsy appear to overlap in those observed in mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) caused by the m.3243A>G mutation and other primary pathogenic mtDNA mutations. 29 However, thalamic (37%) and cerebellar lesions with restricted diffusion are more commonly observed in cases with POLG mutations compared to the m.3243A>G mutation.…”
Section: Discussionmentioning
confidence: 99%
“…69 Our result is consistent with previous observations of a predisposition for occipital lobe involvement in POLGrelated epilepsy, especially among those with juvenile and adult onset, in terms of clinical, radiologic, and histopathologic findings; however, the precise explanation of such preferential involvement remains enigmatic. 12,70 The stroke-like lesions in POLG-related epilepsy appear to overlap in those observed in mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS) caused by the m.3243A>G mutation and other primary pathogenic mtDNA mutations. 29 However, thalamic (37%) and cerebellar lesions with restricted diffusion are more commonly observed in cases with POLG mutations compared to the m.3243A>G mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of VPA can also lead to worsening of an underlying mitochondrial disorder . It has been suggested that POLG1 gene testing should be performed for all patients with suspected mitochondrial disease before starting VPA therapy …”
Section: Discussionmentioning
confidence: 99%
“…37,38 It has been suggested that POLG1 gene testing should be performed for all patients with suspected mitochondrial disease before starting VPA therapy. 6,[12][13][14][15] Sensitivity to VPA toxicity associated with mitochondrial disease has raised the question of whether nonpathogenic POLG1 variants can genetically predispose otherwise healthy patients to adverse effects of VPA. In contrast with the present results, a prospective study by Stewart et al suggested that the common heterozygous POLG1 p.Q1236H variant was strongly associated with hepatotoxicity via VPA-induced nonapoptotic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Presentations range from childhood onset Alpers-Huttenlocher syndrome to adult-onset sensory ataxic neuropathy dysarthria and ophthalmoplegia (SANDO). [4][5][6][7][8][9] Epilepsy is a common presentation of POLG mutations. 6,7 In the majority of patients there is an occipital EEG focus, causing occipital seizures, which are characterised by flickering coloured lights, often persistent for long periods of time; in addition there may also be nystagmus, metamorphopsias and ictal visual loss.…”
Section: Discussionmentioning
confidence: 99%